Application of the Fifth-Generation Cardiac Contractility Modulation Device in a Patient with Chronic Heart Failure: A Case Report - Xie C; Xiang Y; Wu Y; Zhang Y (International Medical Case Reports Journal)
Cui Xie,1 Yang Xiang,1 You Wu,1 Youen Zhang1,2 1Institute of Clinical Medicine and Department of Cardiology, Renmin Hospital, Hubei University of Medicine, Shiyan, Hubei, 442000, People’s Republic of China; 2Arteriosclerosis Cardiovascular Disease Clinical Medical Research Center of Hubei Province, Shiyan, Hubei, 442000, People’s Republic of ChinaCorrespondence: Youen Zhang, Email zye112@hotmail.comAbstract: We present a patient of a 46-year-old female patient was admitted to our hospital due to chest tightness and shortness of breath that lasted for over a month. Echocardiography revealed left-ventricle diameter (anteroposterior) of 54 mm, electrocardiogram showed sinus bradycardia, and QRS duration of 90 ms. The patient experienced no chest tightness or shortness of breath, and there was a marked improvement in exercise tolerance and quality of life after cardiac contractility modulation implantation.Keywords: heart failure, cardiac contractility modulation, dilated cardiomyopathy, ventricular remodeling